The Effect of Digital Absence and Leadership on Employee Performance through Work Discipline at the Ministry of Religious Affairs, Pasangkayu, West Sulawesi - Hatta, Muhammad; Gunawan, Hendra; Rosanti, Novita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of the digital attendance system and leadership on employee performance, with work discipline as a mediating variable at the Ministry of Religious Affairs Office in Pasangkayu Regency, West Sulawesi Province. The research is grounded in the growing need for bureaucratic reform, enhanced employee accountability, and the adoption of digital systems to improve work monitoring and efficiency within government institutions. The expansion of digital public administration highlights the importance of accurate, transparent, and tamper-resistant attendance systems that support reliable employee supervision. At the same time, leadership plays a crucial role in shaping behavioral commitment, strengthening compliance with organizational rules, and encouraging a productive and performance-oriented work environment. A quantitative research method was applied using Structural Equation Modeling–Partial Least Squares (SEM-PLS), with data collected from 142 employees through questionnaires distributed between June and July 2024. The findings reveal that both the digital attendance system and leadership exert a positive and significant influence on employee performance, both directly and indirectly through work discipline. The results further demonstrate that accurate and technology-based attendance mechanisms enhance punctuality and accountability, while effective leadership characterized by communication, role modeling, and motivation strengthens organizational engagement. This study concludes that integrating technological monitoring tools with leadership development is essential for fostering a high-performance organizational culture and advancing modernization within public sector governance. The implications suggest that policymakers should simultaneously prioritize digital infrastructure and leadership capacity-building to sustainably improve employee performance outcomes.